2012
DOI: 10.1116/1.4706894
|View full text |Cite
|
Sign up to set email alerts
|

Scanning transmission electron microscope analysis of amorphous-Si insertion layers prepared by catalytic chemical vapor deposition, causing low surface recombination velocities on crystalline silicon wafers

Abstract: Microstructures of stacked silicon-nitride/amorphous-silicon/crystalline-silicon (SiNx/a-Si/c-Si) layers prepared by catalytic chemical vapor deposition were investigated with scanning transmission electron microscopy to clarify the origin of the sensitive dependence of surface recombination velocities (SRVs) of the stacked structure on the thickness of the a-Si layer. Stacked structures with a-Si layers with thicknesses greater than 10 nm exhibit long effective carrier lifetimes, while those with thin a-Si la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The dark contrast in this study is similar to the results found in damage formation promoted by nitrogen atoms during electron beam irradiation. 26,27 Nitrogen atoms were introduced into the silicon substrates during PECVD process and the crystalline defect might be formed by electron irradiation. On the other hand, hydrogen atoms could be introduced into the near-surface region of silicon substrates during the plasma process.…”
Section: Resultsmentioning
confidence: 99%
“…The dark contrast in this study is similar to the results found in damage formation promoted by nitrogen atoms during electron beam irradiation. 26,27 Nitrogen atoms were introduced into the silicon substrates during PECVD process and the crystalline defect might be formed by electron irradiation. On the other hand, hydrogen atoms could be introduced into the near-surface region of silicon substrates during the plasma process.…”
Section: Resultsmentioning
confidence: 99%
“…[23] Another technique that has been used for SHJ production is catalytic chemical vapor deposition (cat-CVD). [24] TCO layers on the front and rear sides are deposited by a physical vapor deposition process (PVD), either magnetron sputtering or reactive plasma deposition. Finally, the electrodes are made by methods such as screen printing, where a low-temperature curing silver paste is usually printed.…”
Section: Specification Of Shj Solar Cellsmentioning
confidence: 99%
“…The plasma-free CVD deposition such as cat-CVD has been used to deposit high-quality passivation layers. [24,127] The thickness and sharpness of the epitaxial layer on the surface of c-Si can be determined by using conventional high-resolution TEM (HRTEM). [117,124,128] According to an investigation by Matsumura et al, the cat-CVD can realize very sharp a-Si:H/c-Si interfaces and thin transition-layers from c-Si to a-Si:H (<0.6 nm), which is 1.8 nm for PECVD.…”
Section: Cu-electroplated Electrodesmentioning
confidence: 99%
“…14 All these experiments including the present Cat-doping demonstrates that foreign atoms can be incorporated into c-Si at low temperatures when it is exposed to species generated by catalytic cracking reactions with heated W catalyzer. Although the mechanism is not clearly explained, it is clear that the phenomena concerned with low-temperature doping surely exist.…”
Section: Mechanism Of Cat-dopingmentioning
confidence: 99%